CRYSTALLOGRAPHIC BASIS OF POLYTYPISM AND TWINNING IN MICAS - Nespolo M.; Ďurovič S. (My University, 2002)
Although the investigation of micas dates back to the pre-scientific era (see Cipriani, this volume), the idea of polytypism (originally not distinguished from “polymorphism”) in the micas did not ensue until 1934, when Pauling proposed it in a private conversation quoted by Hendricks and Jefferson (1939). The existence of several structural types was however known from goniometric measurements and morphological analysis performed in the 19th century (e.g., Marignac 1847; Baumhauer 1900) and collected in the 4th volume of the Atlas der Krystallformen (Goldschmidt 1918; for a comparative review and later measurements see Peacock...